1982
DOI: 10.1017/s0022172400069862
|View full text |Cite
|
Sign up to set email alerts
|

Campylobacter jejuniand salmonella in raw red meats. A Public Health Laboratory Service Survey

Abstract: SUMMARYThirty-one laboratories examined a total of 6169 meat samples, 1236 from abattoirs and 4933 from retail and other outlets. Campylobacterjejuni was isolated from 98 (16 %). A higher isolation rate of 49/1236 (40 %) was found among abattoir than among retail and other samples (49/49331-0 %). Twenty-two of the laboratories looked for salmonella; although 94/4002 (2-3 %) were positive, in only one sample of minced beef were campylobacter and salmonella found together. Isolation rates for salmonellae were 75… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
1

Year Published

1985
1985
2003
2003

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 10 publications
2
17
0
1
Order By: Relevance
“…This higher isolation rate is probably due to the use of more sensitive culture methods. However our results confirm the conclusions of Turnbull & Rose (1982) that minced meat and sausage meat produced in the U.K. are infrequently contaminated with campylobacters. In Sweden, Svedham, Kaijser & Sjorgen (1981) isolated C. jejuni from all nine samples of minced meat that they tested.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This higher isolation rate is probably due to the use of more sensitive culture methods. However our results confirm the conclusions of Turnbull & Rose (1982) that minced meat and sausage meat produced in the U.K. are infrequently contaminated with campylobacters. In Sweden, Svedham, Kaijser & Sjorgen (1981) isolated C. jejuni from all nine samples of minced meat that they tested.…”
Section: Discussionsupporting
confidence: 90%
“…Although the incidence of salmonella in red meats (including offal) and sausage meat have been the subject of several studies (Dixon & Peacock, 1965;Roberts et al 1975;Abbott & Robertson, 1980;Banks & Board, 1983) there has been only one large scale study of the incidence of campylobacters in these food products (Turnbull & Rose, 1982). These authors indicated that campylobacters could be found in I 000 of minced beef, 0 3 0o of minced pork and 0-1 o of sausage meats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is also a local preference for food to be 'well done' and for people to eat more red meat than chicken-factors which would reduce the risk of acquiring campylobacter infection from meat and poultry. Red meats are in general much less frequently contaminated with campylobacter than poultry (Hudson & Roberts, 1982;Turnbull & Rose, 1982). There are no official figures available on consumption of poultry in N. Ireland but figures from mainland Britain show some variation among different regions, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…La bacteria también puede encontrarse en aguas contaminadas desencadenando en ocasiones grandes brotes de enteritis (12). Los animales que se consideran de mayor importancia son las mascotas; las aves de corral son la fuente más frecuente de infección de muchos países (13) y la bacteria se encuentra en la carne que se contamina con la manipulación, aunque en el momento de la venta gran parte de la contaminación ha desaparecido (14); la gente que tiene contacto con los animales o la carne presenta evidencia de una aumentada exposicibn a la infección (15), aunque en los casos clínicos no se pueda establecer un real contacto con estos animales.…”
Section: Introduccionunclassified